Enabling Mobile Location Based Services for Emergency Cases - Kamarudin, Noraziahtulhidayu; Salam, S. (Service and Innovation in Information Systems (ICRIIS11), 2011)
Late attention by officers in charge to high volumes of crimes and emergency cases can lead to an increase of unsolved cases nationwide. In this paper, we propose the use of Pull & Push Location Based Service model in experiments of the implementation of Location Based Service environment to lessen the problems faced by Police and Fire Fighters in retrieving accurate information while patrolling high risk area. The time taken and the accuracy of information are problems normally faced by Police and Fire Fighters in Emergency Case department. It is crucial for them to get the right information at the right time to their walkie talkie or mobile phones. We first proposed the usage of RSS as the web services to provide feeds for the smart phone application. Updates on crimes or emergency cases within the users’ locations are sent upon users’ retrieval or push based on the users’ locations. The application is developed by using Eclipse IDE platform and tested using HTC Magic with Android OS. The application flow starts by retrieving the location position and information on emergency cases will then be displayed according to date listed. The conceptual design and architecture are designed for Pull and Push Location Based Services.